2018
DOI: 10.1097/wnr.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical grey matter structures in multiple sclerosis

Abstract: The present study aimed to investigate altered grey matter (GM) and functional connectivity (FC) in deep subcortical areas, such as the thalamus and basal ganglia, and their relationship with cognitive impairment (CI) in multiple sclerosis (MS). Thirty-six patients were neuropsychologically assessed, classified as cognitive preserved (CP) and CI, and were compared with 18 healthy controls. GM atrophy and FC were observed in 10 predefined functional areas of the thalamus and in six of basal ganglia. GM atrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies of cognition in MS use a vast array of definitions of cognitive impairment (7–9), as reflected in this review. For example, of the studies using the BRB-N to assess cognitive function, most use a more conservative definition of cognitive impairment of at least 2 SDs below controls on 2 or more tests (23,36,6773), but other, less conservative definitions are used too (37,74,75). The definition of cognitive impairment has been shown to have effects on underlying FC alterations of MS CI by the classification used (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of cognition in MS use a vast array of definitions of cognitive impairment (7–9), as reflected in this review. For example, of the studies using the BRB-N to assess cognitive function, most use a more conservative definition of cognitive impairment of at least 2 SDs below controls on 2 or more tests (23,36,6773), but other, less conservative definitions are used too (37,74,75). The definition of cognitive impairment has been shown to have effects on underlying FC alterations of MS CI by the classification used (76).…”
Section: Discussionmentioning
confidence: 99%
“…BRB-N to assess cognitive function, most use a more conservative definition of cognitive 3 impairment of at least 2 SDs below controls on 2 or more tests(23,36,(67)(68)(69)(70)(71)(72)(73), but other, less 3 conservative definitions are used too (37,74,75). The definition of cognitive impairment has been3 shown to have effects on underlying FC alterations of MS CI by the classification used (76).…”
mentioning
confidence: 99%
“…Studies of cognition in MS use a vast array of definitions of cognitive impairment (7-9), as reflected in this review. For example, of the studies using the BRB-N to assess cognitive function, most use a more conservative definition of cognitive impairment of at least 2 SDs below controls on 2 or more tests (23,36,(67)(68)(69)(70)(71)(72)(73), but other, less conservative definitions are used too (37,74,75). The definition of cognitive impairment has been shown to have effects on underlying FC alterations of MS CI by the classification used (76).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, male MS patients showed a higher degree of GM volume in the bilateral frontal areas and increased functional connectivity as a compensatory mechanism when compared with female patients (Sanchis-Segura et al, 2016). Moreover, in another study, it was shown that GM loss in the thalamus and basal ganglia was associated with worse cognition in MS (Cruz-Gomez et al, 2018).…”
Section: Multiple Sclerosis Brain Pathology: Gray Mattermentioning
confidence: 93%
“…In fact, they found a strong correlation between overall dysfunction and longer MRI changes in several cortical areas that strikingly overlap with regions of the default-mode network, known to be highly critical for attention and memory (e.g., precuneus/posterior cingulate cortex that forms a major hub, medial prefrontal cortex, medial temporal lobe, and lateral and inferior parietal cortex) (Louapre et al, 2016). It was shown that GM loss in the thalamus and basal ganglia is associated with worse cognition in MS (Cruz-Gomez et al, 2018). Furthermore, Cristina Forn reported that GM atrophy is circumscribed to the bilateral posterior cingulate gyrus/precuneus in patients with early MS (Baltruschat et al, 2015).…”
Section: Multiple Sclerosis Brain Pathology: Gray Mattermentioning
confidence: 99%